STUDIES OF ELECTRICAL DOUBLE-LAYER INTERACTIONS IN CONCENTRATED SILICA SOLS BY SMALL-ANGLE NEUTRON-SCATTERING - Penfold, J; Ramsay, J (1985)
Effects of ionic strength, volume fraction and pH on the interparticle interactions in concentrated silica sols of different particle size have been investigated by small-angle neutron scattering. The results have been modelled using the solution of the mean spherical approximation (MSA) of Hayter and Penfold and Hansen and Hayter. In this model the pair potential comprises a hard core and a soft tail, due to the screened coulombic repulsion between the electrical double layers surrounding the spherical particles. Closed analytic solutions of the structure factor, S(Q), for this potential have been used in the fits to the experimental scattering data to obtain the surface charge and potential of the silica particles. Although the surface charge so obtained rises with increases in the pH of the sols, as expected, values are markedly less than the total surface charge density of silica as previously reported.